2011
DOI: 10.1111/j.1741-4369.2011.00595.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring quality, framing what we know: a critical discourse analysis of the Common Inspection Framework

Abstract: In “Measuring quality: framing what we know” I offer a critique of Success in Adult Literacy, Numeracy and ESOL provision (Success in ALNE) – a contextualised reworking of the common inspection framework. This document offers a government‐sponsored account of what quality means when applied to the teaching of adult language, literacy and numeracy. The paper draws on critical discourse analysis to argue that the writers of Success in ALNE imagine an ideal reader, inviting the actual reader to fall in with the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Our study shows how such seepage happens in one specific albeit important instance of the representation of the natural world and its relationship with the social world in a science textbook. In this regard, our study follows a well‐established trail in CDA where in‐depth, single‐case‐study investigations have shown how discourses do their work in representing and producing the world we live in (e.g., refer to de los Heros, ; Dennis, ; Merkl‐Davies & Koller, ). Thus, it is our hope that once readers are able to see how the theorized “universal” particularizes itself in one context through naturalist generalization (Stake, ) they will be able to transfer, adapt, and apply explanations emerging from our study to their own and other contexts.…”
Section: Methodsmentioning
confidence: 98%
“…Our study shows how such seepage happens in one specific albeit important instance of the representation of the natural world and its relationship with the social world in a science textbook. In this regard, our study follows a well‐established trail in CDA where in‐depth, single‐case‐study investigations have shown how discourses do their work in representing and producing the world we live in (e.g., refer to de los Heros, ; Dennis, ; Merkl‐Davies & Koller, ). Thus, it is our hope that once readers are able to see how the theorized “universal” particularizes itself in one context through naturalist generalization (Stake, ) they will be able to transfer, adapt, and apply explanations emerging from our study to their own and other contexts.…”
Section: Methodsmentioning
confidence: 98%
“…They want to better understand how they are constructed/designed to help people gain access and/or better understand why powerful discourses hold the persuasive power that they do. Examples of studies that examine the discursive construction of policies include Dennis (), Gibb (), Hamilton and Pitt (), Johnson (, ), and Yamagami (). Other literacy researchers are interested in specific genres, such as young adolescent literature (e.g., Glenn, ; R. Rogers & Christian, ; Schieble ), or the notion of genre itself (e.g., Schaenen, ).…”
Section: Resultsmentioning
confidence: 99%
“…The key findings in the set of LED studies that drew on written texts ( N = 40) tended to coalesce around seven major themes, with a few of the studies generating findings with overlapping themes. These key themes included issues of social justice or equity relating to education in general or to teaching and learning among youths and adult learners, with the following categories of findings: Learning across social differences (Fernsten, ; Gebhard et al., ; Hammond, ; Hashimoto, ; Johnson, , ; Marshall & Toohey, ; Powell, ; Schieble, ) Transformations in learner identity (Chen, ; Fernsten, , ; Goulah, ; Menard‐Warwick & Palmer, ; R. Rogers, ; Schmidt & Whitmore, ) Curricular materials and discourses (Dennis, ; Glenn, ; Hashimoto, ; Marshall & Toohey, ; R. Rogers & Christian, ; Schieble, ; Schmidt, ; Taylor, ; P.A. Young, ) Transformations in teacher identity (Cahnmann, Rymes, & Souto‐Manning, ; Davison, ; Moin et al., ; van Rensburg, ) Power and agency variability within specific contexts and/or discourses (Anderson, ; Gibb, ; Marshall & Toohey, ; R. Rogers, ) Movement or lack of movement across social class or socioeconomic identities (Anderson, ; Dutro, ; Dworin & Bomer, ) Processes of assessment (Prins & Toso, ; Tuten, ) …”
Section: Resultsmentioning
confidence: 99%
“…Public scrutiny based on quantitatively derived notions of quality induces a climate of fear in the UK provoking disparate professional reactions: strategic compliance, cynicism, hijacking, commitment or passive resistance , Dennis, 2012. While conceptions of quality are subject to on-going contestation (Dennis, 2011), OfSTED's judgements about an organization can make or break professional careers, can result in the closure of a college or department, can have a devastating impact on personal, professional or organisational reputations through naming and shaming. OfSTED grades the work of all state funded establishments including adult and further education from within a onedimensional four-part scale (where one is outstanding and four inadequate) on a tri-annual cycle according to an excessive 200 quality criteria.…”
Section: Relational and Networked Positioningmentioning
confidence: 99%